Hubungan Kejadian Stres dan Kejadian Emotional Eating dengan Status Gizi pada Remaja SMA di Kecamatan Banjarsari Surakarta - Devira Novi Aprillia; Dyah Intan Puspitasari; Dwi Sarbini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Stress management or coping strategies of stress are individual efforts to manage the emotional pressure they experience. One form of coping strategy that is often practiced is emotional eating, the behavior of overeating arising from emotional factors. This behavior can affect nutritional status. Therefore, this study aims to determine the relationship between stress levels and emotional eating with nutritional status in high school adolescents. This type of research is observational analytic with a quantitative approach and the research design used a cross-sectional study design. This study was conducted in two locations, namely SMA Muhammadiyah PK Kottabarat Surakarta and MAN 1 Surakarta, with a total of 154 respondents selected using a proportional random sampling technique. The instruments used included the Depression Anxiety Stress Scale for Youth (DASS-Y 21) and the Adult Eating Behavior Questionnaire (AEBQ) as well as anthropometric measurements. Data analysis was carried out univariately and bivariately using the Spearman Rank correlation test. The research findings show no significant relationship between stress levels and nutritional status (p-value = 0.629), and between emotional eating and nutritional status (p-value = 0.051). Therefore, it can be concluded that there is no statistically significant relationship between stress events and emotional eating behavior and nutritional status in high school adolescents. This is because stress factors and emotionally triggered eating behavior do not directly affect adolescents' nutritional status in this context. These findings demonstrate the importance of monitoring students' stress levels, which can influence emotional eating, which in turn can affect nutritional status.